Ecological Water Level Determination and Safeguard Measures for Rivers in Northern Jiangsu Plain - WANG Zhenqi; FANG Hongyuan; XU Guangdong; ZHU Ye; WANG Chengjie (Renmin Zhujiang)
Effective methods of calculating the threshold of river ecological flow (water level) need to be employed to obtain measures of controlling the ecological state of rivers in a plain river network and to build a robust long-term mechanism of ecological flow control.The Zongliutang River in the river network area of Northern Jiangsu Plain is divided into upper,middle,and lower reaches according to its objective environment and its actual operation and management situation.Then,the controlling condition of the ecological water level of each reach is analyzed respectively.Considering the hydrological characteristics,hydrodynamic characteristics,and observed hydrological data conditions of rivers in this river network area,several methods are utilized to calculate the ecological water level threshold of the middle reach of the river respectively.Those methods include the annual minimum water level method with a 90% guarantee rate,the wetted perimeter method,the minimum monthly average water level method,and the lowest survival water depth method.Through the comparative analysis of actual river operation and management schemes,the ecological water level targets of the upper,middle,and lower reaches of the river are comprehensively determined as 17.40 m,8.96 m,and 7.50 m respectively.After the control value of the ecological water level of the river is obtained by comprehensive analysis,the actual operation and management situation of the river is taken into account to propose specific safeguard measures for maintaining the ecological water level (flow) target of the river from multiple perspectives.Some of the measures are constructing a robust and feasible ecological flow control system,accelerating the construction of an information monitoring system of ecological flow and water intake and an early warning system safeguarding the ecological water level target,and strengthening the supervision and assessment of the implementation of river and lake ecological flows (water levels).